2011
DOI: 10.1088/0957-4484/22/25/254024
|View full text |Cite
|
Sign up to set email alerts
|

NonlinearIVrelations and hysteresis in solid state devices based on oxide mixed-ionic–electronic conductors

Abstract: The current-voltage, I-V, relations as well as the defect distributions are calculated for solid state devices in which the acceptors are mobile. The devices are of the metal|oxide|metal (MOM) type, where the oxide is a mixed-ionic-electronic conductor. The electrodes are blocking for material exchange. I-V relations are calculated for cyclic voltammetry, high amplitude ac voltage and low amplitude ac voltage from which the ac impedance is derived. The results exhibit nonlinear I-V relations, energy storage, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…A similar behavior is found in series C, but with some slightly hysteresis effects. These behaviors suggest that during these measurements the sample had a low ionic mobility that did not lead to an important ionic redistribution on the time scale of measurements [5,16]. Anyway, it should be noted that I(t) exhibits a great diversity of shapes, therefore indicating that ion motion is taking place.…”
Section: Temporal Variation Of Current Intensitymentioning
confidence: 86%
See 3 more Smart Citations
“…A similar behavior is found in series C, but with some slightly hysteresis effects. These behaviors suggest that during these measurements the sample had a low ionic mobility that did not lead to an important ionic redistribution on the time scale of measurements [5,16]. Anyway, it should be noted that I(t) exhibits a great diversity of shapes, therefore indicating that ion motion is taking place.…”
Section: Temporal Variation Of Current Intensitymentioning
confidence: 86%
“…The intensity discontinuity observed in series B in the range between 17 and 22 V is remarkable, in such a way that in order to recover the increasing behavior of I with increasing V m , the application of higher voltages is necessary. This suggests some kind of memory or resistance switching effect [16] that would be associated with the ionic motion. An alternative approach for studying the different changes taking place in the sample is to compute the parameter R s = V m /I.…”
Section: Temporal Variation Of Current Intensitymentioning
confidence: 99%
See 2 more Smart Citations
“…Each sodalite cage and channel contains eight cations and one cation respectively inside and the remaining 24 cations are located inside the cavity facing the sodalite cages . Due to pore opening of the zeolites they are used for a wide range of applications such as gas separation and adsorption, ion exchange and catalysis . It has already been reported that water molecules can easily diffuse inside the cavity and cages.…”
Section: Introductionmentioning
confidence: 99%